Automatic ELCB switching / Hasan Mohamad Ali & Mohamad Luqman Hakim Hakbar - Mohamad Ali, Hasan; Hakbar, Mohamad Luqman Hakim (2015)
An Earth Leakage Circuit Breaker (ELCB) is an electrical device that disconnects protected circuit whenever it detects unbalance current between the phase's conductor and the neutral conductor. Such an unbalance is sometimes caused by current leakage through the body of a person who is grounded when accidentally touching any active current of the circuit. A lethal shock can result from these conditions. ELCB are designed to disconnect this fault fast enough to prevent the harm caused by such shocks. Apparently, there is no one had commercial the Earth Leakage Circuit Breaker (ELCB) with auto switching features in the market. The current ELCB that available in the market is a manual type and cannot differentiate between temporary disturbances and permanent faults. Its means that, if a disturbance or fault occurs on the protected area (house or shop), the protection system will force ELCB to trip. One of the drawbacks of the common ELCB is that, it's can't tum on the power supply back to the normal operation condition although only a short disturbance occurs. Such disturbance is lightning strike on the transmission line in the distribution site near to the protected area. To tum the power back to normal operation, consumers need to do that manually. In order to solve that problem, Automatic ELCB Switching had been developed. This thesis presents the development of the ELCB system. This device was designed to differentiate between permanent fault and short disturbances (lightning).